A checklist for model credibility, salience, and legitimacy to improve information transfer in environmental policy assessments. (September 2016) - van Voorn, G.A.K.; Verburg, R.W.; Kunseler, E.-M.; Vader, J.; Janssen, P.H.M.
Abstract: Modelers involved in environmental policy assessments are commonly confronted with the lack of uptake of model output by policy actors. Actors have different expectations of models, condensed into three quality criteria: credibility, salience, and legitimacy. The fulfilment of quality criteria is also dynamic as expectations vary, change, and possibly counteract each other. We present a checklist for modelers involved in model-based assessments that is aimed at the identification and monitoring of issues, limitations and trade-offs regarding model quality criteria. It draws upon the literature of integrated assessments as well as case study analysis of environmental policy assessments for the Dutch government, based on expert interviews and embedded experience. The checklist is intended to be consulted during assessments; its application may result in greater awareness among modelers involved in assessments regarding model quality criteria, and may positively affect the uptake of model-based knowledge from environmental policy assessments by policy actors. Highlights: Model credibility, salience and legitimacy are affected by various factors. Factors are summarized based on interviews, literature and a case study. A model evaluation checklist for modelers is presented to help detect such factors. The checklist may improve the uptake of model-based output by decision makers.